A Pilot E-Cigarette Voucher Scheme in a Rural County of the United Kingdom. Issue 3 (14th October 2022) - Notley, Caitlin; Belderson, Pippa; Ward, Emma; Wade, James; Clarke, Hannah
Abstract: Introduction: E-Cigarette voucher schemes have been piloted across the UK to support populations to quit smoking. This short report evaluates a scheme that targets vulnerable and disadvantaged smokers who had failed to quit smoking by other means. Methods: Descriptive summary evaluation of service data on smoking outcomes and qualitative data from selected participants, as "key-informants" ( n = 4) and key stakeholders (stop smoking staff, vape shop staff, and general practitioners [GPs]). Results: In total, 668 participants were referred to the scheme, and 340 participants redeemed a voucher. By intention to treat analysis (ITT) 143/668 (21%) were recorded as quit smoking at 4 weeks. At 12 weeks, 7.5% of participants had quit, by ITT. Overall, the pilot project was well received by clients as it offered an affordable route into vaping for smoking cessation. GPs supported the scheme and appreciated being able to offer an alternative to entrenched smokers. Conclusions: The scheme shows promise in supporting entrenched smokers to quit smoking. The offer of similar voucher schemes across the UK suggests the potential to reduce overall smoking prevalence and associated morbidity and mortality. Implications: Working with GPs in a deprived area, it was possible to set-up a vape shop voucher scheme for smoking cessation. Patients with comorbidities who had tried and failed to quit smoking previously were referred to receive a vape shop voucher to be redeemed for an initial starter kit, alongside support from the stop smoking service. This innovative scheme enabled 42% of entrenched smokers who redeemed a voucher to successfully quit smoking within 4 weeks.